Male circumcision as a measure to control HIV infection and other sexually transmitted diseases. - Quigley, M; Weiss, H; Hayes, R (2001)
There is growing epidemiological evidence from sub-Saharan Africa that male circumcision reduces the risk of HIV acquisition. We review the recent evidence of the protective effect on HIV and other sexually transmitted diseases, including discussion of possible biological mechanisms and highlighting the limitations of the observational studies on which these findings are based. We conclude by discussing the public health implications of these findings, including issues such as safety, acceptability, feasibility and cost-effectiveness of promoting male circumcision in African populations.